Sense of Coherence and Burnout in Healthcare Professionals in the COVID-19 Era - Stoyanova, Kristina; Stoyanov, Drozdstoy Stoyanov (Frontiers in Psychiatry, 2021)
Emotional exhaustion in the context of vulnerability to burnout is a part of the universal narrative of high stress and systematically reported in health care professionals. The Sense of Coherence (SOC) is a salutogenic construct, operationalized by A. Antonovsky as a Generalized Resource for Resistance (GRR) to stress in three dimensions: meaningfulness (Me) – the desire of a person to be motivated to cope, comprehensibility (C) – the belief that the challenge is understood and manageability (Ma) – the belief that coping resources are available. The relation between SOC and the dimensions of burnout – Emotional Exhaustion (EE), Depersonalization (D) and Personal Accomplishment (PA), is a part of salutogenic functioning, which reveals the inner motivation and self-organization of the psycho-emotional energetic resource. This study traces the salutogenic functioning of Bulgarian health care professionals during the pandemic. A general psychological background of coherence and exhaustion has been identified. All components of the sense of coherence were positively correlated to Personal Accomplishment. Emotional Exhaustion and Depersonalization correlated negatively with coherence. SOC was validated as a possible determinant to predict the reduction of exhaustion and depersonalization as well as high levels of professional performance. The dimension of Meaningfulness in the coherence phenomenon was demonstrated to have the highest predictive value for professional burning.